Interference between higher education and the needs of society: The example of the professionalizing master’s degree : "Sustainable management of waste in urban areas" - Bouadam , Roukia (Journal of Human Sciences, 2020)
In this new context marked by societal, economic, environmental and technological changes, training appears as a major issue of membership between the professional and academic world. The Algerian university, like other universities in the world, is concerned by the consideration of this new data in training offers and the development of training curricula. Through these recent training offerings, Constantine3 University aims to support these new changes, through professional-oriented university training in the image of the professional Master’s degree on "sustainable waste management in urban areas". The interest of this article is to present this experience by highlighting its necessity and the approach adopted in the process of its elaboration in order to put the university at the service of society.